A comparison of the effects of chemical sympathectomy by 6-hydroxydopamine in newborn and adult rats - Finch, L. (1973)
1. The effects of chemical sympathectomy with 6-hydroxydopamine (6-OHDA) on the cardiovascular system of the rat were compared in, (a) 10-week-old rats treated during the first 14 days after birth with 150 μg/g subcutaneously, and (b) adult rats injected intravenously with 2 × 50 mg/kg on day 1 and 2 × 100 mg/kg on day 7 and the experiments performed on day 8. 2. Intravenous administration of 6-OHDA to adult rats almost completely abolished the pressor responses to stimulation of the entire sympathetic outflow in the pithed rat, the contractions of the lower eyelid to stimulation of the cervical sympathetic trunk and the vasconstrictor responses produced by periarterial nerve stimulation of the isolated renal artery preparation. Pressor responses to physostigmine and to tyramine were markedly reduced or abolished in anaesthetized and pithed rat preparations, respectively. 3. In corresponding experiments, 10-week-old rats treated as newborns with 6-OHDA showed a marked reduction in the stimulation-induced pressor responses and contractions of the lower eyelid, but completely normal vasoconstrictor responses to periarterial nerve stimulation of the isolated perfused renal artery were obtained. The pressor responses to physostigmine were slightly reduced but the tyramine responses were unchanged. 4. Treatment with 6-OHDA at birth caused an almost complete and long-lasting noradrenaline depletion in the heart, spleen, salivary glands and ileum but only a partial depletion in the mesentery from 10-week-old rats. These low noradrenaline levels showed no recovery in rats up to an age of 4 months. The tyrosine hydroxylase activity in both the cervical and stellate ganglia from 10-week-old rats was markedly reduced by treatment with 6-OHDA after birth. 5. Injections of 6-OHDA after birth produce an almost complete and permanent sympathectomy of various adrenergically innervated organs in the rat. The vascular system represents a major exception, exhibiting a surprisingly high resistance to this type of chemical adrenergic denervation.